Sensorineural hearing loss in the acute phase of a single episode of acute otitis media - Kasemodel,Ana Luiza Papi (2020)
Abstract Introduction: Acute otitis media is a disease with high global prevalence, that can lead to several acute complications and auditory sequelae. Data regarding the auditory evaluation in the acute phase of acute otitis media are scarce. Objective: To evaluate the main audiometric changes (air and bone conduction thresholds) in the initial phase of an acute otitis media episode. Methods: A case-control study was performed. Patients diagnosed with acute otitis media with less than 7 days of evolution in relation to the complaint onset were selected, and healthy volunteers were selected as controls. The acute otitis media and control groups were submitted to pure tone and vocal audiometry. Results: The acute otitis media group included a total of 27 patients (30 ears). Hearing loss was present in 90.0% of the ears with acute otitis media, with conductive loss in 14 (46.67%) and mixed loss in 13 (43.33%). Both the air and bone conduction thresholds obtained with the tonal audiometry in the acute otitis media group were significantly worse than the controls at all tested frequencies (p< 0.05). In patients with acute otitis media, we observed that the thresholds for frequency >1 kHz (bone conduction) and 3 kHz (air conduction) were significantly worse in patients with tinnitus compared to patients without tinnitus. Conclusion: During the first 7 days of evolution after the onset of an isolated episode of acute otitis media, we observed significant increases in bone and air thresholds at all frequencies, especially >2 kHz, compared to healthy ears.